2019
DOI: 10.1038/s41438-019-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

MdGSTF6, activated by MdMYB1, plays an essential role in anthocyanin accumulation in apple

Abstract: Anthocyanins are biosynthesized on the cytosolic surface of the endoplasmic reticulum and then transported into the vacuole for storage. Glutathione S -transferases (GSTs) are considered to be responsible for the transport of anthocyanins into the vacuole. However, the regulatory mechanisms of GSTs in plants are still unclear. Here, we performed a genome-wide analysis and identified 69 GST genes in apple. The expression of MdGSTF6 was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 62 publications
18
122
0
Order By: Relevance
“…Earlier work in litchi revealed that the expression of LcGST4 was also activated by LcMYB1 (Hu et al, 2016). Similar results were also reported in strawberry, apple, tea and kiwifruit (Jiang et al, 2019;Liu et al, 2019;Luo et al, 2018;Wei et al, 2019). Data from the dual-luciferase assays performed in this study suggested that the transcriptional activity of the PpGST1 promoter is directly up-regulated by PpMYB10.1 rather than PpMYB10.2 and PpMYB10.3, and it was further activated by PpbHLH3 through the interaction between PpMYB10.1 and PpbHLH3.…”
Section: Expression Of Gst Is Regulated Via Different Meanssupporting
confidence: 88%
See 4 more Smart Citations
“…Earlier work in litchi revealed that the expression of LcGST4 was also activated by LcMYB1 (Hu et al, 2016). Similar results were also reported in strawberry, apple, tea and kiwifruit (Jiang et al, 2019;Liu et al, 2019;Luo et al, 2018;Wei et al, 2019). Data from the dual-luciferase assays performed in this study suggested that the transcriptional activity of the PpGST1 promoter is directly up-regulated by PpMYB10.1 rather than PpMYB10.2 and PpMYB10.3, and it was further activated by PpbHLH3 through the interaction between PpMYB10.1 and PpbHLH3.…”
Section: Expression Of Gst Is Regulated Via Different Meanssupporting
confidence: 88%
“…Heterologous overexpression of VviGST4 ( Vitis vinifera ) and AcGST1 ( Actinidia chinensis ) in Arabidopsis tt19 mutant can functionally complement both the anthocyanin‐less phenotype in plant and the PA‐deficient phenotype in seed coat (Liu et al , ; Pérez‐Díaz et al , ). However, in this study, PpGST1 only possessed the capacity to functionally complement the anthocyanin‐less phenotype of Arabidopsis tt19 mutant but not the PA‐deficient phenotype in the seed coat, which was similar to the result of An9 ( Petunia hybrida ), LcGST4 ( Litchi chinensis ), RAP ( Fragaria ananassa ), CsGSTF1 ( Camellia sinensis ) and MdGSTF6 ( Malus domestica ) in the tt19 complementation assay (Hu et al , ; Jiang et al , ; Kitamura et al , ; Luo et al , ; Wei et al , ). These data indicated that PpGST1 plays a pivotal role in anthocyanin transport and differed from AtTT19 , VviGST4 and AcGST1 which also participate in seed deposition of PAs.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations